Interiority, Traslación, and the Devotion to the Black Nazarene - Calano, Mark Joesph T (Archīum Ateneo, 2020)
The play in the performance of panatà to the Black Nazarene in Quiapo, Manila, demonstrates an authentic religiosity that is manifested in materiality, and a modernity that is indigenous. The paper operates within the framework of a panatà (devotion) as: (1) a personal (even inherited) secret vow; (2) that is performed publicly; and (3) is directed towards touching and being touched by God. The first part discusses the dynamics of how petition and thanksgiving are interior movements that reflect útang-na-loób (debt of gratitude) as dasál (prayer). But this movement, although essentially personal and secret, can only be expressed in the communal and public performance of the yearly procession (traslación). The second part discusses this public and communal “translation” of the Black Nazarene as a construction of a relationship with the sacred that is embodied and embedded. And the third part investigates the encounter (hierophany) through the appropriation of the poón (icon) within the dynamics between hirap (difficulty, suffering, poverty) and ginhawa (rest, relief, ease) in the kalye (streets) of Manila.